Relationship between maximum mean pressure and peak pressure obtained by digital manometer during maximal respiratory pressure - Montezzo, Dayane; Lages, Ana Clara; Terra Criollo, Carlos Julio; Veloso, Marcelo; Britto, Raquel Rodrigues; Parreira, Verônica Franco (Journal of Respiratory and CardioVascular Physical Therapy, 2012)
Background: Measurement of Maximal Respiratory Pressure (MRP) by manometers is a useful procedure in evaluating respiratory muscle strength. Digital manometers allow the acquisition of pressure curves and calculation of several variables, among them Maximal Mean Pressure (MMP) and Peak Pressure (PP). Objective: The main objective was to determine if a difference exists between the variables MMP and PP during the MRP measurement, using different interfaces, as well as establish whether there is an association between values observed. Methods: Fifty healthy, non-obese, active volunteers were assessed, with a mean age of 26±5 years and confirmed normal pulmonary function. A digital manometer and four different interfaces were used to measure MRP. The paired t-test was applied to compare MMP and PP and Pearson’s correlation was used to evaluate the association between the two variables, with a significance level of 0.05. Results: Comparison between MMP and PP for both maximal inspiratory pressure and maximal expiratory pressure showed a significant difference in the four interfaces studied (p<0.001). A high-magnitude correlation was recorded when comparing the two variables for both MRP tests (r=0.99; p<0.001). Conclusion: MMP demonstrated a significant correlation with PP. Thus, the latter may be an alternative for measuring MRP in specific cases, since a strong association was observed with MMP despite the significant difference.